DO MEMES IMPACT BRAND COOLNESS PERCEPTIONS? EXAMINING HEDONIC VERSUS UTILITARIAN PRODUCTS - Aleem, A.; Loureiro, S. M. C.; Aguiar, M. (15th Annual Conference of the EuroMed Academy of Business, 2022)
Digital platforms are one of the best tools to connect consumers worldwide (Nieubuur, 2021). Specifically, in the first quarter of 2021, Facebook alone had an active user base of 2.91 billion users, YouTube had 2.29 billion active users, while Instagram had 1.39 billion active users (Statista, 2021). Following Chuah et al. (2020), content is key in the digital environment. With such high numbers of online users, and the need for keeping them interested, memes became a frequently used content to interact with consumers. Internet Memes (IMs) usually take the form of animations, GIFs, videos, images, and image macros. As IMs are flexible, and able to relate to many expressions (e.g., humour, advice, irony, sarcasm), brands can easily integrate IMs in their strategy. Besides establishing a connection between brands and consumers worldwide, social media also allows users to check the latest trends, and most importantly, what is cool nowadays. Coolness reflects consumers’ perceptions of a brand or product’s quality, distinctiveness, or novelty (Sundar et al., 2014). Thus, being a cool brand and having cool content is becoming increasingly important to managers and practitioners. IMs are easy to understand, fun, “shareable” and can have a positive impact on consumer behaviour (Nieubuur, 2021). Brand Coolness (BC) also shows to have a positive impact on the consumer decision-making process (Warren et al., 2019). However, there is a gap in the literature concerning the relationship between IMs and BC perceptions. Although there is a variety of studies concerning BC effects on consumer decision making, to our knowledge, there is no literature establishing a connection between IMs and BC. Thus, the present study aims to understand if IMs influence consumers’ BC perceptions, in the context of hedonic versus utilitarian personal beauty items. A survey was conducted, to assess the impact of utilitarian (Colgate) and hedonic (Dior) brands through IMs. A multiple linear regression was performed to predict brand coolness perceptions on hedonic versus utilitarian brands, with and without the meme. Our findings suggest that, when not using a meme, the utilitarian brand (Colgate), is associated with the energetic and authentic characteristics. On another hand, when the brand uses the meme, the brand coolness perceptions are explained by the useful/extraordinary and original dimensions. As for the hedonic brand, when not using the IM, the brand (Dior) is associated with energetic, authentic, and iconic brand coolness dimensions. However, when using the IM, the hedonic brand is associated with useful/extraordinary, energetic, popular, and subcultural dimensions. Our results are in accordance with the brand coolness and internet memes’ literature: (1) brands do not need to be associated with the ten coolness characteristics, since the perception of BC differs from brand to brand, and across consumers (Warren et al., 2019); (2) IMs have specific characteristics (such as iconicity, humour, popularity, (Chuah et al., 2020), it was expected that introducing them would change consumers perceptions. We also acknowledge the importance of the results to academics and practitioners. To our knowledge, this is the first attempt to analyse specific dimensions of brand coolness in the context of hedonic versus utilitarian products as reflected by IMs, contributing to the marketing and branding literature. As for managers, brands can use digital marketing channels to enhance popularity through IMs. As IMs can take many forms and is easily adapted, the tool is a cool way of advertising our products. Plus, it is easy to share between consumers, which increases chances of becoming viral through social media.